2021
DOI: 10.3390/ani11020571
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Detection of GDF9 Gene and Its Association with Litter Size in Luzhong Mutton Sheep (Ovis aries)

Abstract: Litter size is one of the most important economic traits in sheep. GDF9 and BMPR1B are major genes affecting the litter size of sheep. In this study, the whole coding region of GDF9 was sequenced and all the SNPs (single nucleotide polymorphisms) were determined in Luzhong mutton ewes. The FecB mutation was genotyped using the Sequenom MassARRAY®SNP assay technology. Then, the association analyses between polymorphic loci of GDF9 gene, FecB, and litter size were performed using a general linear model procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
2
24
1
Order By: Relevance
“…The obtained data prove the feasibility of studying the influence of the gene GDF9 on the meat rate productivity of sheep of other breeds, in particular, A alleles and AA and AG genotypes. This is also promising from the point of view that a range of researches have demonstrated that the AG genotype has a positive effect on fertile multiplicity of ewes [20,21,22]. All thing being equal, getting more lambs provides increase of mutton rate production, which largely determines the economic efficiency of meat sheep farming.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The obtained data prove the feasibility of studying the influence of the gene GDF9 on the meat rate productivity of sheep of other breeds, in particular, A alleles and AA and AG genotypes. This is also promising from the point of view that a range of researches have demonstrated that the AG genotype has a positive effect on fertile multiplicity of ewes [20,21,22]. All thing being equal, getting more lambs provides increase of mutton rate production, which largely determines the economic efficiency of meat sheep farming.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of studies witness a link between the growth differentiation factor gene and the reproductive qualities and fertile multiplicity of sheep [20,21,22]. It has been shown that GDF9 expression is significantly higher in ovarian tissues than in other body tissues, while the protein product of the gene plays an important role in maintaining the normal folliculogenesis [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The fixed model was y = μ + G1 + G2 + G1G2 + e , where y is the phenotypic value of litter size, μ is the population mean, G1 is the fixed effect for FecB genotype or GDF9 genotype, G2 is the fixed effect for BMP15 genotype, G1G2 is the fixed interaction effect of FecB and BMB15 combined genotypes or GDF9 and BMB15 combined genotypes and e is the residual error. The GDF9 and FecB data were analyzed in our previous report [ 23 ], and results indicated that the SNPs ENSOART00000014382.1:c.994G>A (rs421019907) and c.978A>G (rs399579080) in the GDF9 gene were significantly associated with litter size. Because these two SNPs are linked, we selected one of them (c.994G>A) to analyze its interaction with the SNPs in BMP15 .…”
Section: Methodsmentioning
confidence: 99%
“…The Luzhong mutton sheep is a new breed, and it has high fertility and meat production performance. It was developed by crossbreeding Hu sheep from China with White-headed Dorper sheep from South Africa [ 23 ]. Litter size records of Luzhong mutton sheep showed large variations between individual ewes, ranging from one to four.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation